2006
DOI: 10.1128/aem.72.4.2390-2393.2006
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Life Cycle of Tuber magnatum

Abstract: Tuber spp. are ectomycorrhizal ascomycetes that produce ascocarps known as truffles. Basic aspects of Tuber biology have yet to be fully elucidated. In particular, there are conflicting hypotheses concerning the mating system and the ploidy level of the mycorrhizal and truffle hyphae. We used polymorphic microsatellites to compare the allelic configurations of asci with those from the network of the surrounding hyphae in single Tuber magnatum truffles. We then used these truffles to inoculate host plants and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
118
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 26 publications
3
118
1
1
Order By: Relevance
“…Moreover, it has been possible to widen the range of known truffle hosts: they are traditionally associated with trees and shrubs, but have now also been located inside orchid roots (Selosse et al, 2004), suggesting that truffles possess a more flexible host range. Only recently has the truffle's complex life cycle been elucidated, underlining that they are primarily haploid and reproduce by outcrossing (Paolocci et al, 2006). Unlike T. melanosporum, which can be cultivated in orchards by inoculating oaks and hazelnuts with spore suspensions (Chevalier, 1994), Tuber magnatum, the most expensive and appreciated truffle species, has so far resisted the charms of domestication.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been possible to widen the range of known truffle hosts: they are traditionally associated with trees and shrubs, but have now also been located inside orchid roots (Selosse et al, 2004), suggesting that truffles possess a more flexible host range. Only recently has the truffle's complex life cycle been elucidated, underlining that they are primarily haploid and reproduce by outcrossing (Paolocci et al, 2006). Unlike T. melanosporum, which can be cultivated in orchards by inoculating oaks and hazelnuts with spore suspensions (Chevalier, 1994), Tuber magnatum, the most expensive and appreciated truffle species, has so far resisted the charms of domestication.…”
Section: Introductionmentioning
confidence: 99%
“…The white truffle (Tuber magnatum) is the most valuable species and fortunately peculiar to our country. It is however difficult to achieve in truffle for the hard artificial mycorhization (Mello et al, 2001;Paolocci et al, 2006). This is definitely an advantage for domestic production, which may qualify as the right ecological conditions (Zambonelli et al, 2012).…”
Section: Mushrooms and Trufflesmentioning
confidence: 99%
“…Contrary to the above, Paolocci et al [22] and Rubini et al [23] using microsatellite markers, demonstrated that some, and possibly considerable, outcrossing takes place in T. magnatum. According to the authors, the vegetative infecting mycelium is homokaryotic, originating from a single ascospore germination.…”
mentioning
confidence: 94%
“…In addition, Paolocci et al [22] and Rubini et al [23] demonstrated that single mycorrhized root tips harbored only one combination of marker alleles, indicating that the mycorrhizing agent is a homokaryotic, monosporic mycelium. This is certainly compelling (though the use of microsatellites as markers could be viewed as problematic owing to the possibility of instability of microsattelite markers, especially during meiosis).…”
mentioning
confidence: 99%